Analysis of Location Quotient (LQ) and Beef Cattle Value Chain in Woha, Monta, and Bolo Districts, Bima Regency - Kharismafullah Kharismafullah; Khairunnisah Khairunnisah; Andy Hermawan (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the comparative advantage of beef cattle in three livestock center subdistricts of Bima Regency, namely Woha, Monta, and Bolo, using the Location Quotient (LQ) approach and a value chain analysis of beef cattle producers in Bima Regency. The LQ analysis was conducted by comparing the contribution of the beef cattle population in each subdistrict to the total beef cattle population in Bima Regency and West Nusa Tenggara Province. The results show that the three subdistricts have LQ values > 1, indicating that beef cattle are a basic commodity in the region. This study also examines the beef cattle value chain in Bima Regency, which has not yet been efficient due to limitations in technology, productivity, and the bargaining position of farmers. Strengthening an integrated upstream–downstream system is required to increase value added and regional economic competitiveness.